Braiding intensity analysis of a post-seismic debris flow event using a comprehensive indexing tool - Rosdianah Ramli; Janice Lynn Ayog; Ngui Min Fui Tom; Rodeano Roslee; Felix Tongkul; Mohammad Radzif Taharin (Horizon Research Publishing, 2025)
River braiding occurs when sediment accumulates in a river section, resulting in bar formations that divide the flow into multiple channels, a phenomenon quantified as braiding intensity. This intensity is measured using a braiding index (BI), a metric essential for understanding sediment dynamics in braided rivers. While several braiding indices have been developed, many overlook key factors, such as the area occupied by bars, and often lack defined limits or unit-free properties, limiting their flexibility across diverse river types. Furthermore, conventional indices struggle to detect variations in braiding intensity in river reach sections with differing widths. Addressing these limitations, Das and Islam introduced a comprehensive, four-part braiding index tool that accommodates bar area, defined limits, and unit-free characteristics, enhancing its adaptability across various river conditions. However, this braiding index tool has not been applied for non-regulated, post-seismic flow events. Therefore, this study applies this novel braiding index tool to the Panataran river located in Sabah, Malaysian Borneo, a river significantly impacted by a 2015 post-seismic debris flow event, causing notable changes in its braiding river morphology. Using high-resolution satellite imagery, the study evaluates four distinct braiding indices— BI*, BI1, BI2 and BI3—across six sections of the river, capturing both pre- and post-seismic debris flow conditions. Results reveal that the tool effectively quantifies changes in bar formation and channel flow patterns, especially highlighting increased sediment deposition up to 42% in downstream sections. These findings hold practical implications for local stakeholders, including ecotourism operators and environmental authorities, providing essential data to identify erosion-prone areas or regions favorable for sustainable ecotourism development. By demonstrating the tool's ability to measure and monitor morphological changes in post-seismic river systems, this research underscores its broader utility in flood disaster response and vulnerability assessment, river management, and environmental planning, paving the way for future applications in other river systems affected by seismic events and similar geomorphological challenges.